2020
DOI: 10.4314/ejhs.v30i6.8
|View full text |Cite
|
Sign up to set email alerts
|

Client Factors Affect Provider Adherence to Guidelines during First Antenatal Care in Public Health Facilities, Ethiopia: A Multi-Center Cross-Sectional Study

Abstract: BACKGROUND፡ Timely entry to an antenatal care with a healthcare provider who follows a set of national guidelines is assumed to ensure higher levels of client satisfaction. It is also expected to improve perinatal outcomes. Little is known about the level of adherence of Ethiopian providers to these guidelines. Therefore, this study aims to assess the proportion of clients who received complete (100%) provider adherence to antenatal care guidelines at the first visit and client associated factors in Gondar Tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The current study demonstrates that the odds of the utilization of early ANC visits were 13% less likely among women whose households were headed by the male as compared to their counterparts. This finding was in agreement with other study findings at which husbands' permission had a tremendous impact on the utilization and timing of ANC services [62][63][64]. Another study done by Mulat G., et al noted that the odds of using ANC visits were more likely among womens' who had autonomy on their healthcare decision-making as compared to their counterparts [65].…”
Section: Discussionsupporting
confidence: 91%
“…The current study demonstrates that the odds of the utilization of early ANC visits were 13% less likely among women whose households were headed by the male as compared to their counterparts. This finding was in agreement with other study findings at which husbands' permission had a tremendous impact on the utilization and timing of ANC services [62][63][64]. Another study done by Mulat G., et al noted that the odds of using ANC visits were more likely among womens' who had autonomy on their healthcare decision-making as compared to their counterparts [65].…”
Section: Discussionsupporting
confidence: 91%
“…Although participants acknowledged the benefits of using ANC guideline, their level of adherence to national ANC guideline during first visit as it was surprisingly low at the four study facilities [ 27 ]. Through our findings, we have learned more from the participants themselves about their reasons for not following the guideline.…”
Section: Discussionmentioning
confidence: 99%
“…More than one in four (26%) Ethiopian women do not receive any ANC visits at all, and even those who receive it do not get quality services due to providers’ inability to adhere to focused ANC guideline [ 18 , 26 ]. As an example, a cross-sectional study done in Gondar town indicated that only 32% of women received complete providers’ adherence to national ANC guideline during the first visit [ 27 ]. However, the reasons for the poor adherence to ANC guideline are not well known.…”
Section: Introductionmentioning
confidence: 99%
“…The observation checklist, scoring criteria and the entire method for the baseline of the cohort study have been described elsewhere. 20 …”
Section: Methodsmentioning
confidence: 99%
“…The observation checklist, scoring criteria and the entire method for the baseline of the cohort study have been described elsewhere. 20 Covariates Several explanatory variables were included as covariates. These include a range of maternal socio-demographic variables such as maternal age, residence, religion, marital status, educational level and employment status.…”
Section: Primary Exposure Variablementioning
confidence: 99%